One- and two-dimensional Fourier transform infrared correlation spectroscopy of Phyllagathis rotundifolia - Chuah, C.H.; Tan, H.P.; Ling, S.K. (Elsevier, 2011)
1D- and 2D-IR with thermal perturbation was utilized in this study for the macroscopic fingerprinting of Phyllagathis rotundifolia. Conventional FTIR spectroscopy showed limited spectral differences for the species with a closely related species, Phyllagathis praetermissa.However, the visual 2D-IR spectra were able to enhance IR absorptions and generate characteristic IR fingerprint for P. rotundifolia. This approach combined with PCA is also applicable to detect mixtures of P. rotundifolia and P. praetermissa. By using this non-destructive IR fingerprinting, the identification and quality control of P. rotundifolia can be achieved more effectively.